HYPERBOLIC EXPRESSIONS USED IN SONG LYRIC OF WESTLIFE’S COAST TO COAST ALBUM - Syukur Mei Zai (Universitas Nias Raya, 2024)
This research was aimed at analysing hyperbolic expressions used in song lyric of Westlife’s Coast to Coast album. This research was designed by using qualitative descriptive method. In analysing the data, the researcher used theory of Creswell. The source of data in this study was taken from the song lyric of Westlife’s Coast to Coast album that was obtained from internet by downloaded the lyric from the song. The data of this study are word, phrase, and sentence in the lyrics that contained the album. Hyperbole is one kind of figure of speech that exaggerates things with overstatement. Based on the result of research is the hyperbole there are 23 expressions. There are expressions in the form of word, phrase, and sentence. It can be concluded that each song lyric Westlife’s Coast to Coast album made by hyperbole to make the song interesting to hear and allows listeners to feel the emotions that convey of singers or songwriters such as deep sadness, extraordinary happiness, or various other feelings. It is suggested to use the song as media of teaching semantics, especially figure of speech.